Apoptosis in nonalcoholic fatty liver disease: diagnostic and therapeutic implications. (April 2011) - Alkhouri, Naim; Carter-Kent, Christine; Feldstein, Ariel E
Pathological increases in cell death in the liver as well as in peripheral tissues has emerged as an important mechanism involved in the development and progression of nonalcoholic fatty liver disease (NAFLD). An increase in hepatocyte cell death by apoptosis is typically present in patients with NAFLD and in experimental models of steatohepatitis, while an increase in adipocyte cell death in visceral adipose tissue may be an important mechanism triggering insulin resistance and hepatic steatosis. The two fundamental pathways of apoptosis, the extrinsic (death receptor-mediated) and intrinsic (organelle-initiated) pathways, are both involved. This article summarizes the current knowledge related to the distinct molecular and biochemical pathways of cell death involved in NAFLD pathogenesis. In particular, it will highlight the efforts for the development of both novel diagnostic and therapeutic strategies based on this knowledge.